2019
DOI: 10.1002/gps.5164
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an in‐home respite care program to support informal dementia caregivers: A comparative study

Abstract: Objectives Dementia is a major public health problem with important physical, psychosocial, emotional, and financial consequences for patients, their caregivers, and society. Since patients prefer to be managed at home, extensive research has been conducted into effectiveness of psychosocial interventions to support informal caregivers. The aim of this study was to assess the effectiveness of an in‐home respite care program. Methods In a prospective quasi‐experimental study, 99 dyads who received an in‐home re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…The modest but clinically significant benefits of CARITAS were similar to extant dementia case management, which aimed to enhance patients’ QOL ( d = 0.05) and caregivers’ QOL ( d = 0.21) and lower caregiving burden ( d = 0.12) [36]. Moreover, these effects were also comparable to other forms of non-pharmacological interventions, such as caregivers’ education to improve patient’s QOL ( d = 0.24) [37], home-based respite care programmes to alleviate caregiver burden ( d = 0.30) [38], PCC training ( d = 0.30) to reduce behavioural concerns such as agitation [37], notwithstanding that this evaluation did not involve a control group.…”
Section: Discussionmentioning
confidence: 96%
“…The modest but clinically significant benefits of CARITAS were similar to extant dementia case management, which aimed to enhance patients’ QOL ( d = 0.05) and caregivers’ QOL ( d = 0.21) and lower caregiving burden ( d = 0.12) [36]. Moreover, these effects were also comparable to other forms of non-pharmacological interventions, such as caregivers’ education to improve patient’s QOL ( d = 0.24) [37], home-based respite care programmes to alleviate caregiver burden ( d = 0.30) [38], PCC training ( d = 0.30) to reduce behavioural concerns such as agitation [37], notwithstanding that this evaluation did not involve a control group.…”
Section: Discussionmentioning
confidence: 96%
“…Nonetheless, previous studies aimed at identifying the effectiveness of inhome respite care in Taiwan did not examine the impact on caregiver burden (Chen & Chiou, 2015;Chen & Huang, 2010). Other research showed no considerable effects of inhome respite care on caregiver burden (Vandepitte et al, 2019). In a previous study for in-home respite care users in Taiwan, the researchers found that "accessibility" and "availability" are the two aspects where users reported the lowest satisfaction (Chen & Chiou, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, only one quantitative study focusing on in-home respite care was included in that review, and it showed that vulnerable caregivers in the intervention group have low plasma epinephrine values after 2 weeks of respite care (Grant et al, 2003). Vandepitte et al (2019) conducted a comparative study to assess the effectiveness of an in-home respite program for dementia caregivers. This comparative study did not show a significant difference in the total caregiver burden between the intervention and control groups after 6 months; however, the desire of the intervention group to institutionalize the patient is significantly lower than that of the control group (Vandepitte et al, 2019).…”
mentioning
confidence: 99%
“…The baseline data from a prospective study titled 'Effectiveness and cost-effectiveness of an in-home respite care program in supporting informal caregivers of people with dementia' were used [17,18]. Detailed information on the study aim and methodology can be consulted in the protocol paper by [19].…”
Section: Methodsmentioning
confidence: 99%